The User Satisfaction Perspectives of the Information System Projects - A’ang Subiyakto Subiyakto; Abd. Rahman Ahlan Rahman Ahlan; Mira Kartiwi; Syopiansyah Jaya Putra; Yusuf Durachman (Institute of Advanced Engineering and Science, 2016)
It is inevitable that information system (IS) has been the essential role in the management and academic functions of the higher education institutions (HEIs) in developing countries, like Indonesia. In this country, despite the IS project developments have been performed since 1980s, but its performances tended still low. The efforts have been performed for responding this issue, but the studies have been remained in limited number. Accordingly, this study was carried out to know what factors that influence the satisfactions, in respect of its significant effects towards the project performances. The internal stakeholders were the population, which was sampled using the purpose random sampling. The 52 (87%) paper based data and the 61 (9%) online ones were then used in the data analysis stage with the partial least squares-structural equation modeling (PLS-SEM) method. The results revealed that, besides the system and service qualities directly affected the endogenous variable, the institutional contexts also indirectly influenced the variable. The study remained limitations, but its findings may theoretically and practically contributes towards the user satisfaction measurement, especially from the perspectives of the Islamic HEIs in Indonesia.